AN ACCURATE SOLUTION FOR THE TWODIMENSIONAL MODEL OF ALBITE USING STATISTICAL MECHANICS (Journal of Sciences, Islamic Republic of Iran)
A two-dimensional model of Al, Si ordering in alkali feldspar is formulated and used to calcul~tea ccurately the configurational entropy for the model. For this purpose, a new method called Independent Basic Unit or IBU is introduced. To compare the results with the exact values, this method is applied to the onedimensional model of albite. The results given by IBU are found to be accurate to the extent that the deviation in free energy is less than 0.8%. The reduced configurational entropy is calculated to 'be 1.065 corresponding to 8.854 J K-1 mol-1 for the two-dimensional model. This value is within 6% of standard values obtained by using approximate calculations for the same model